ASSESSING THE DIMENSION OF SACRAL SPINAL CANAL FOR THECALOSCOPY USING MRI - ABHIMANYU PRADHAN; SUSHIL YADAV (International Journal of Pharma and Bio Sciences, 2016)
Endoscopy of the lumbar sub-arachnoidal space is named thecaloscopy, which has been used for diagnostic and therapeutic purposes. The understanding of the anatomic dimensions of this region is useful for the atraumatic use of flexible endoscopes. Furthermore, by using MRI the determination of anatomic values of the sacral spinal canal is possible without the use of cadaver measurements. MRI of lumbo-sacral region was performed on 25 male and 25 female patients who were referred by treating doctor. Measurements were performed on T2 weighted mid-sagittal image. The dimensions measured were sacral Spinal Canal (SSC), Sacral Spinal Process (SSP) and the width of sacral hiatus. The mean length of sacral spinal canal in its center for male was 76.34±5.091 (range 67.8-91) and for female was 74.276±6.775 (range 59.8-86.7). The mean length of the sacral spinal process for male was 70.608±5.861 (range 55.1-88.0) and for female was 67.592±7.436 (range 53.6-82.3). The width of sacral hiatus was 17.32±1.730 mm for male and 17.08±1.868 mm for female. Also the Lumber Sacral Angle were measured whose mean for female was 61.28±8.681 and for male was 53.24±6.488. Trans-sacral endoscopy though sacral hiatus is anatomically possible to perform because the endoscope can be introduced through the sacral hiatus over a length of sacral spinal canal. No further means needs to be undertaken during thecaloscopy, since the difference between sexes for the measured diameters is not statistically significant.